Development of water and energy-saving measures for large pumping stations - Fakhriddin J. Nosirov; Oleg Ya. Glovatsky; Ravshan K. Dusmatov; Jurabek A. Uralov (PROBLEMS OF ENERGY AND SOURCES SAVING, 2026)
Relevance: in recent years, in connection with the energy transition taking place in many countries worldwide, this process in Uzbekistan has been carried out with an intellectualization of key energy efficiency issues. This is particularly true for the operation of large pumping stations. Such stations operate in cross-border regions. The largest unique pumping stations of the Amu-Bukhar, Amuzang, and Karshi cascades operate in Turkmenistan. Analysis of global trends indicates potential for expanding the use of mobile power units. The use of mobile power units for agriculture and water management should be most developed, with an increase in the reliability of the mobile energy service system. The development of innovative technology, including the justification of the structure and technical service specialized in servicing mobile power units, is a pressing issue of scientific and practical significance. Aim: development and implementation of innovative technology for a mobile energy service system to improve the reliability and energy efficiency of pumping units. Methods: international experience and comparative analysis of methods for controlling the main parameters of pumps are used to ensure regulation of energy savings Results: the present research was conducted to create favorable conditions for the implementation of artificial intelligence technologies for energy resource management and optimization of energy efficiency of pump operation. The main direction for increasing the efficiency of the mobile energy service system is the modeling of optimal operating modes of systems, taking into account the probabilistic nature of changes in the operating factors.